2010
DOI: 10.1167/iovs.09-4759
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topographies of Glaucoma Drainage Devices and Their Influence on Human Tenon Fibroblast Adhesion

Abstract: The most frequently implanted glaucoma drainage devices are of markedly different surface topography. Surface roughness appears to correlate with tenon fibroblast adhesion in vitro and also with the rate of occurrence of postimplantation hypertensive phase and failure due to fibrous encapsulation. Surface roughness may thus play a role in triggering excessive fibrovascular reactions. Smoother base plate surfaces may enhance the success rates of these devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…The different designs of the implants could also play a role. The Ahmed tube is valved and might induce more fibrosis compared to the non-valved BV glaucoma implant (Choritz et al 2010). Another possible explanation for the difference in EC loss might be the different material of the glaucoma drainage devices.…”
Section: Discussionmentioning
confidence: 99%
“…The different designs of the implants could also play a role. The Ahmed tube is valved and might induce more fibrosis compared to the non-valved BV glaucoma implant (Choritz et al 2010). Another possible explanation for the difference in EC loss might be the different material of the glaucoma drainage devices.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Furthermore, electron microscopy comparing the Ahmed-FP7 end plate with the Baerveldt-350 implant found that it had a root-mean-square roughness 10-fold greater, resulting in increased in vitro tenon fibroblast adhesion. 34 Antimetabolites have been trialed in aqueous drainage device implantation to prevent encapsulation but failed to show improved IOP and had a higher incidence of hypotony and graft melt. 5,8,32 Bleb histology has been cited as an important factor in the long-term success of aqueous drainage devices, with encapsulation reducing filtration and increasing the need for medications.…”
Section: Discussionmentioning
confidence: 99%
“…These include its large surface area, low, curved profile, and polished surface. 9,10 In addition, it has been postulated that complete occlusion of non-valved implants such as the BGI for the first four to six weeks postoperatively limits inflammatory mediators from entering the bleb with the consequent reduction in the likelihood of bleb encapsulation. 11 Success rates reported for the AGV range from 68 to 100% and for the BGI from 43 – 100% with such rates being highly dependent upon the length of follow-up, type of glaucoma, and success criteria.…”
mentioning
confidence: 99%